Chapter: 'DojoIBL: Nurturing Communities of Inquiry' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Stefaan Ternier; Angel Suarez; Fleur Prinsen; Marcus Specht (Springer Nature, 2021)
This paper presents and outlines the demonstration of DojoIBL, a web-based platform that aims at nurturing communities of inquiry by supporting communication and collaboration with emerging technological affordances. The manuscript briefly elaborates on the theoretical underpinning of DojoIBL and describes the functionalities supported. It concludes anticipating the follow up implementation which will consist on the integration of role support in DojoIBL.